2020
DOI: 10.3390/ijns6040082
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Assessing the Cost-Effectiveness of Newborn Screening: The Example of Congenital Adrenal Hyperplasia

Abstract: Generalizing about the cost-effectiveness of newborn screening (NBS) is difficult due to the heterogeneity of disorders included in NBS panels, along with data limitations. Furthermore, it is unclear to what extent evidence about cost-effectiveness should influence decisions to screen for specific disorders. Screening newborns for congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency can serve as a useful test case, since there is no global consensus on whether CAH should be part of NBS panels.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 102 publications
(197 reference statements)
0
8
0
1
Order By: Relevance
“…Earlier studies reported CAH screening would be either unlikely to be cost-effective or cost-effective only if a single test is performed [19,38]. While recent studies in Canada, Brazil and Sweden concluded that NBS screening for CAH enables to reduce morbidity and mortality [39,40] as well as costs associated with adverse outcomes, transportation, and hospitalization length [41]. The long-term health benefits of NBS for CAH are unknown and should be addressed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies reported CAH screening would be either unlikely to be cost-effective or cost-effective only if a single test is performed [19,38]. While recent studies in Canada, Brazil and Sweden concluded that NBS screening for CAH enables to reduce morbidity and mortality [39,40] as well as costs associated with adverse outcomes, transportation, and hospitalization length [41]. The long-term health benefits of NBS for CAH are unknown and should be addressed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…We tried to adjust the cut-off threshold in relation to GA [14], but a significant reduction in recall rate, especially between preterm newborns, was only achieved in 2017, when we routinely implemented the LC-MS/MS second-tier test in the workflow. Furthermore, scientific literature has acknowledged the importance of LC-MS/MS in improving the specificity of CAH newborn screening [4, 17-19, 21, 37] and in reducing both the overall economic costs, since it makes confirmatory tests less frequently needed [38], and the emotional burden bore by families when a newborn is recalled for further diagnostic ascertainments. In addition, two-tier testing strategy has the advantage of reducing the duration of follow-up in newborns with positive CAH screening [25].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated levels of 17OHP may be associated with 3βHSD2 deficiency due to peripheral conversion by the 3βHSD type I enzyme. High 17OHP levels are false positives for 21OH deficiency in neonatal screening programs according to some of the mentioned studies [ 5 , 60 , 101 , 102 , 103 , 104 ]. Certain countries introduced screening protocols based on 17OHP immunoassays (dried blood spot) which are less useful in non-severe cases and non-classical forms of 21OH deficiency and non-21OH types [ 24 , 103 , 105 ].…”
Section: Discussionmentioning
confidence: 99%